Ultrasensitive Field‐Effect Biosensors Enabled by the Unique Electronic Properties of Graphene. Issue 15 (8th October 2019) - Zhang, Xiaoyan; Jing, Qiushi; Ao, Shen; Schneider, Grégory F.; Kireev, Dmitry; Zhang, Zhengjun; Fu, Wangyang
Abstract: This review provides a critical overview of current developments on nanoelectronic biochemical sensors based on graphene. Composed of a single layer of conjugated carbon atoms, graphene has outstanding high carrier mobility and low intrinsic electrical noise, but a chemically inert surface. Surface functionalization is therefore crucial to unravel graphene sensitivity and selectivity for the detection of targeted analytes. To achieve optimal performance of graphene transistors for biochemical sensing, the tuning of the graphene surface properties via surface functionalization and passivation is highlighted, as well as the tuning of its electrical operation by utilizing multifrequency ambipolar configuration and a high frequency measurement scheme to overcome the Debye screening to achieve low noise and highly sensitive detection. Potential applications and prospectives of ultrasensitive graphene electronic biochemical sensors ranging from environmental monitoring and food safety, healthcare and medical diagnosis, to life science research, are presented as well. Abstract : This review provides a critical overview of the chemical functionalization, operation, and application of graphene‐based field‐effect transistor devices that are both sensitive and selective, with a particular focus on ultrasensitive biochemical detection enabled by the unique electronic properties of graphene.